A qualitative study of goalkeeper coaches` perceptions of key qualities in talented youth soccer goalkeepers - Steenbok, W.; Kubayi, A.; Morris-Eyton, H.; Stone, J. A. (The Journal of Sports Medicine and Physical Fitness, 2026)
BACKGROUND: Despite a substantial body of literature on identifying talent in outfield players, information on goalkeepers (GKs) is scarce due to the specialist demands associated with the position. The purpose of this study was to explore which qualities GK coaches perceive as important for talented youth soccer GKs.